Adverbial clauses, main clause phenomena, and composition of the left periphery the cartography of syntactic structures - Haegeman, Liliane M. V. (New York ; Oxford : Oxford University Press, 2013)
This title uses the cartographic theory to examine the left periphery of the English clause and compares it to the left-peripheral structures of other languages.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Causative (Linguistics); Grammar, Comparative and general -- Transitivity; Grammar, Comparative and general -- Adverbials